THE INFLUENCE OF PROBIOTIC MEDICINAL PRODUCT PROBION ON HEMATOLOGICAL AND CERTAIN IMMUNOLOGICAL INDICES OF BROILERS - Жила, М. І.; Михалюк, О. В.; Бассараб, В. П.; Максимович, О. А. (Scientific Progress & Innovations, 2013)
The article presents data on the influence of probion on growth dynamics and also hematological indices of broilers on the 15th, 30th and 43rd day of application. It is found that chickens injected with the drug probion more intensively increased average daily gain and body weight.The hemoglobin level was raising, there was increase of leucocyte quantity and phagocytic activity of pseudoeosinophil(e). The biggest difference of indicators was identified in chickens fed with probiotic probion in a dose of 1 g/kg food.